Validation of an OpenSim full-body model with detailed lumbar spine for estimating lower lumbar spine loads during symmetric and asymmetric lifting tasks. Issue 5 (4th April 2019) - Beaucage-Gauvreau, Erica; Robertson, William S. P.; Brandon, Scott C. E.; Fraser, Robert; Freeman, Brian J. C.; Graham, Ryan B.; Thewlis, Dominic; Jones, Claire F.
Abstract: There is currently no validated full-body lifting model publicly available on the OpenSim modelling platform to estimate spinal loads during lifting. In this study, the existing full-body-lumbar-spine model was adapted and validated for lifting motions to produce the lifting full-body model. Back muscle activations predicted by the model closely matched the measured erector spinae activation patterns. Model estimates of intradiscal pressures and in vivo measurements were strongly correlated. The same spine loading trends were observed for model estimates and reported vertebral body implant measurements. These results demonstrate the suitability of this model to evaluate changes in lumbar loading during lifting.